Pelaksanaan Pembelajaran Ansambel Sejenis di Kelas VII.1 SMP Negeri 43 Padang - Fadhila Rizky Maharani; Syeilendra Syeilendra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The aim of this study is to understand and explain the implementation process of ensemble learning of the same type in class VII.1 of SMP Negeri 43 Padang. This research falls into the category of qualitative research using descriptive methods. The researcher themselves serve as the main instrument in this study, supported by writing tools and a camera. Data is obtained through literature review, observation, interviews, and documentation. The data analysis process includes data collection, data reduction, data presentation, and drawing conclusions from the data. At the planning stage, the teacher prepares learning tools according to the independent curriculum included in the teaching module. At the implementation stage of the same ensemble, the teacher uses lecture, question and answer, practice, and demonstration methods. The learning media used by the teacher includes the melodica and the score for the song